Global trends in sarcopenia and cancer over the past 10 years: a bibliometric analysis - Ruoshuang Liu; Menghuan Wu; Xia Cheng; Chundi Zhou; Caiqin Cheng; Lijun Feng; Yirong Shen (Discover Oncology)
Abstract Background Sarcopenia is common among patients with cancer. The alterations in the internal milieu of cancer patients, coupled with the adverse effects of antineoplastic therapies, markedly augment the susceptibility to sarcopenia. We aimed to clarify the current research status and investigate future trends in sarcopenia and cancer research. Methods Publications on sarcopenia and cancer from the past decade were retrieved from the Web of Science database. VOSviewer, CiteSpace, and Bibliometrix R package were used for visualization analysis. Results A total of 3749 publications were retrieved between 2014 and 2023. These publications were written by 21,507 authors affiliated with 4068 organizations in 76 countries/regions. Japan, the United States, and China constituted the primary contributors to the majority of the publications. The top three research institutions with the highest outputs in this field were the University of Alberta, Wenzhou Medical University, and Maastricht University. The Journal of Cachexia Sarcopenia and Muscle served as the pivotal and most cited journal in this field. Baracos VE from the University of Alberta was the author with the most publications. “Sarcopenic obesity”, “Radiomics”, and “Neutrophil/lymphocyte ratio” were highly focused topics in current research. Conclusion This study conducted the first bibliometric analysis of literature on sarcopenia and cancer. A systematic analysis of the present research status and emerging trends in this field provides important references for future research.